Studi Kasus Analisis Kesulitan Siswa dalam Pembelajaran IPS Kelas VI Sekolah Dasar - Jannah, Miftahul; Lasari, Yufi Latmini (Diniyah: Jurnal Pendidikan Dasar, 2023)
Because the material is full of concepts, students often experience difficulties learning social studies. This research aims to determine what factors cause students' difficulties in learning social studies at school and determine solutions that can be provided to overcome these students' learning difficulties based on the teacher's perception. This research is a type of qualitative research conducted at SDN 23 Batusangkar. The research subjects were class VI students. Researchers collected data using in-depth interviews, observation, and documentation. The author uses descriptive analysis techniques through data reduction, data display, and drawing conclusions. Research findings show that two factors cause students' difficulties in learning social studies, namely internal factors that come from within students in the form of a lack of interest and motivation of students in learning social studies and external factors, namely teachers' lack of creativity in using learning media, monotonous teacher teaching, the language of social studies subject matter is too high. Teachers are often unprofessional when teaching in class. Solutions that can be taken to overcome these problems are better classroom management, the teacher's willingness to be creative in methods and use of learning media, and the teacher's ability to create social studies subject matter in class using more straightforward language.Keywords: Social studies, learning difficulties, learning solution